2021
DOI: 10.1097/prs.0000000000008672
|View full text |Cite
|
Sign up to set email alerts
|

Fat Grafting before Delayed Prophylactic Mastectomy and Immediate Implant Reconstruction for Patients at High Risk of Complications

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While mastectomy has been the criterion standard historically, breast conservation therapy (BCT) has emerged as an equally effective treatment. Given the contour deformities that can arise after BCT, autologous fat grafting (AFG) has gained popularity to correct these defects, offering promising results as an innovative reconstructive method with aesthetically pleasing outcomes requiring only a minimally invasive surgery 2,3 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While mastectomy has been the criterion standard historically, breast conservation therapy (BCT) has emerged as an equally effective treatment. Given the contour deformities that can arise after BCT, autologous fat grafting (AFG) has gained popularity to correct these defects, offering promising results as an innovative reconstructive method with aesthetically pleasing outcomes requiring only a minimally invasive surgery 2,3 …”
mentioning
confidence: 99%
“…Given the contour deformities that can arise after BCT, autologous fat grafting (AFG) has gained popularity to correct these defects, offering promising results as an innovative reconstructive method with aesthetically pleasing outcomes requiring only a minimally invasive surgery. 2,3 While AFG offers the potential to correct specific contour deformities after breast procedures and is frequently used as an augment in mastectomy, it is not a standard of care for patients undergoing BCT. Controversy remains regarding the possible long-term implication of autologous fat grafting, particularly relating to cancer recurrence and oncological outcomes-rooted in concern of injecting stem cell containing aliquots into a surgical site that recently housed cancer.…”
mentioning
confidence: 99%
“…Other studies have demonstrated the positive impact of AFT on both the functional and aesthetic outcomes in breast reconstruction [ 56 ]. AFT has also been used prophylactically to reverse the pathologic effects of RIF in breast tissues prior to breast reconstruction [ 57 , 58 , 59 ]. Ribuffo et al demonstrated that two separate AFT procedures to the breasts 6 weeks after RT and 3 months prior to completion of implant-based breast reconstruction dramatically reduced the rates of skin ulceration and implant exposure [ 58 ].…”
Section: Role Of Fat Grafting In Treating Radiation Induced Fibrosismentioning
confidence: 99%
“…For these patients, the risk of early complications, reconstruction failure, and poor aesthetic results can reach up to 50% [ 77 ]. Carrying out AFG, either before the tissue expander is substituted with the definitive implant or even before the prophylactic mastectomy is performed, significantly improved surgical outcomes [ 78 , 79 , 80 ].…”
Section: Autologous Fat Grafting and Hybrid Prepectoral Reconstructionmentioning
confidence: 99%